Discovery of TXS 1515-273 at VHE gamma rays and modelling of its Spectral Energy Distribution - D'Ammando F.; Nabizadeh A.; Bissaldi E.; Orienti M.; Cutini S.; Acciari V.A.; Ansoldi S.; Antonelli L.A.; Arbet Engels A.; Artero M.; Asano K.; Baack D.; et al. (Italy, 2025)
In February 2019, a flaring state of the extreme blazar candidate TXS 1515-273 was registered by the Fermi-LAT, which triggered observations with the MAGIC telescopes and the X-ray satellites Swift, XMM-Newton and NuStar. The observations led to the discovery of the source at very-high-energy (VHE, 100 GeV < E < $ 100 TeV) gamma-ray energies and the detection of short time scales of variability (1 h) in several X-ray bands.
The analysis of the observed variability helped us to constrain the physical parameters of the emission region. Thanks to the high-quality X-ray data, the synchrotron peak location was determined. The
source was classified as a high synchrotron peaked source during the flaring activity. We constructed the broadband spectral energy distribution from radio to TeV. We interpreted it assuming leptonic emission and taking into account the constraints from the X-ray variability. We tested two scenarios: a simple one-zone model and a two-component model. Both models were found to describe the data well from X-ray to VHE gamma ray, but the two-zone model allows for a more accurate modelling of the emission at radio and optical energies.
37th International Cosmic Ray Conference (ICRC2021)